Gold Investment Choice for Gen Z in 2025 - Ivan Saputra (Universitas 17 Agustus 1945 Semarang, 2025)
This study examines the investment preferences of Generation Z, specifically their inclination toward gold investment. The research is based on secondary data obtained through literature studies focusing on Gen Z's investment behavior. The findings indicate that Gen Z tends to favor gold as an investment option due to several compelling reasons. One of the main motivations is the potential for profit, as gold is considered not only a stable asset but also one that offers promising long-term returns. In addition, gold is perceived as a safe investment amid economic uncertainty. Other influencing factors include: (1) security and stability, (2) ease of access and purchase through digital platforms, (3) long-term investment potential, (4) diversification of investment portfolios, (5) historical value and its role as a symbol of security, (6) easy and flexible transactions, and (7) protection against inflation. These factors highlight the strategic thinking of Gen Z investors who seek both financial security and growth through alternative investment instruments such as gold.